POLYAKOV LOG COARSE GARNET OCCURRENCE IN THE SOUTH URALS - V.A. Popov; M.A. Rassomakhin; S.V. Kolisnichenko (Минералогия)
Ontogenic modeling of the origin of coarse garnet of the Polyakov log occurrence (South Urals) in a fine-grained schist sequence allowed the authors to conclude on its metasomatic growth with the replacement of chlorite aggregates. Muscovite, ilmenite, epidote, quartz and apatite remain preserved in the primary schist orientation of individuals. Accessory andesine, cobaltite, pentlandite, pyrrhotite and zircon crystallized together with garnet. The formation of coarse garnet crystals is probably related to fluctuations of supersaturation relative to garnet in areas of schists with abundant chlorite. This allows us to expect the presence of coarse garnet areas in adjacent parts of the schist sequence.